2021
DOI: 10.1002/anie.202111608
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Photoelectrochemical Nanotool for Intracellular Drug Delivery and Evaluation of Treatment Effect

Abstract: With reduced background and high sensitivity, photoelectrochemistry (PEC) may be applied as an intracellular nanotool and open a new technological direction of single‐cell study. Nevertheless, the present palette of single‐cell tools lacks such a PEC‐oriented solution. Here a dual‐functional photocathodic single‐cell nanotool capable of direct electroosmotic intracellular drug delivery and evaluation of oxidative stress is devised by engineering a target‐specific organic molecule/NiO/Ni film at the tip of a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 58 publications
(13 reference statements)
4
58
0
Order By: Relevance
“…The practical applicability of the nanotool was then in vitro studied. Previous reports had revealed the potentialdirected delivery or sampling functions of nanopipettes [2,10,27,28], the function of which was initially investigated using HEPES milieu containing saturated fluorescein. As shown in Figure 2(a), such an effect was verified by 20 min electroosmosis under -1.0 V, which led to obvious green fluorescence of fluorescein within the nanotool.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The practical applicability of the nanotool was then in vitro studied. Previous reports had revealed the potentialdirected delivery or sampling functions of nanopipettes [2,10,27,28], the function of which was initially investigated using HEPES milieu containing saturated fluorescein. As shown in Figure 2(a), such an effect was verified by 20 min electroosmosis under -1.0 V, which led to obvious green fluorescence of fluorescein within the nanotool.…”
Section: Resultsmentioning
confidence: 99%
“…2(e), the HEPES milieu of 60 cP containing 130 mM K + and different Na + concentrations of (i) 2.5 mM, (ii) 10 mM, and (iii) 15 mM were tested, and hardly any signal variation could be observed. Besides, to study the possible pH variation effect, as shown in Figure 2(f), HEPES milieu of 60 cP with pH of 6.6, 7.4, and 7.8 had almost no effect on the response of the nanotool [10,14]. To study the possible adsorption effect, the nanotool was sequentially immersed into the cell lysate for 10 min and then tested for three repeated times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we extended the boundary of current single‐cell electroanalysis by developing a photoelectrochemistry (PEC) nanotool. [ 117 ] At the tip of nanopipette, an organic molecule/NiO/Ni film was engineered, which served as both the biorecognition element and sensitizer to synergize with p‐type NiO. Upon intracellular delivery at picoliter level, the oxidative stress effect caused structural change of the organic probe, switching its optical absorption and altering the cathodic response caused by the photon‐to‐electricity conversion.…”
Section: Nano‐pipette Based Analysismentioning
confidence: 99%